Analysis of Aesthetic Principles in Typography - Fu, Zeya; Wang, Yiying (Transactions on Social Science, Education and Humanities Research, 2023)
With the development of the times, typography has developed from a writing skill to a systematic, diversified and open study. Typographic art, which refers to the overall careful arrangement of Chinese characters according to the basic principles of human vision, is the crystallization of human labor and experience, and is becoming more and more complete with the development of human civilization. Chinese characters are the carriers of Chinese culture, the visual symbols for recording the Chinese language, and the tools for human exchange and communication. The paper combines the research the general overview of the current research status of some domestic experts and scholars on the technology of typeface design, organizes and summarizes the relevant papers, and will launch an in-depth discussion according to the current stage.